Creating Markets in Kenya : Unleashing Private Sector Dynamism to Achieve Full Potential - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
Kenya has the opportunities and resources to stimulate sustainable economic growth and development, but its potential has been constrained by under-investment and low firm-level productivity. Altogether, its development has not been sufficiently sustainable or equitable to transform the lives of ordinary citizens. Poverty remains high, with thirty-six percent of Kenyans living under the national poverty line, whereas the richest ten percent of the population receive forty percent of the nation’s income. This country private sector diagnostic (CPSD) sheds light on how the private sector can more effectively contribute to advancing the country’s developmental goals. Applying a sectoral lens, it puts forward operational recommendations highlighting strategic entry points for diversification and growth and addresses key constraints to private sector engagement. It also seeks to inform World Bank and IFC strategies, paving the way for joint programming to create markets and unlock private sector potential.